2022
DOI: 10.3390/pharmaceutics14040877
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced In Vitro Antiviral Activity of Hydroxychloroquine Ionic Liquids against SARS-CoV-2

Abstract: The development of effective antiviral drugs against SARS-CoV-2 is urgently needed and a global health priority. In light of the initial data regarding the repurposing of hydroxychloroquine (HCQ) to tackle this coronavirus, herein we present a quantitative synthesis and spectroscopic and thermal characterization of seven HCQ room temperature ionic liquids (HCQ-ILs) obtained by direct protonation of the base with two equivalents of organic sulfonic, sulfuric and carboxylic acids of different polarities. Two non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…API-ILs have been prepared from Alzheimer’s and Parkinson’s disease medication, antibiotics, anticancer drugs, antibacterial and antifungal drugs, antihistamine and calcium channel blockers, numerous antimalarial APIs, antivirals, arthritis drugs, beta blockers, drugs for diabetes, gastrointestinal disorders, hyperkalemia, local anesthesia, pain relievers, multiple respiratory disorder medications, supplements, and vitamins, among others. They have been made from compounds such as dextro­methorphan, halofantrine, , hydroxy­chloroquine, rotigotine, ketoprofen, diclophenac, nalidixic acid, donepezil, , rivastigmine, salicylic acid, , and many others. As of January 2023, a Sci-Finder search on the term “API-ILs” provided 98 patents, 2177 research papers, and 289 reviews in which API-ILs were a central theme.…”
Section: Why Study Liquid Salts Of Apis (Api-ils)?mentioning
confidence: 99%
“…API-ILs have been prepared from Alzheimer’s and Parkinson’s disease medication, antibiotics, anticancer drugs, antibacterial and antifungal drugs, antihistamine and calcium channel blockers, numerous antimalarial APIs, antivirals, arthritis drugs, beta blockers, drugs for diabetes, gastrointestinal disorders, hyperkalemia, local anesthesia, pain relievers, multiple respiratory disorder medications, supplements, and vitamins, among others. They have been made from compounds such as dextro­methorphan, halofantrine, , hydroxy­chloroquine, rotigotine, ketoprofen, diclophenac, nalidixic acid, donepezil, , rivastigmine, salicylic acid, , and many others. As of January 2023, a Sci-Finder search on the term “API-ILs” provided 98 patents, 2177 research papers, and 289 reviews in which API-ILs were a central theme.…”
Section: Why Study Liquid Salts Of Apis (Api-ils)?mentioning
confidence: 99%
“…Faı ´sca et al [57] have reported the repurposing of the antimalarial drug, hydroxychloroquine (HCQ), as an efficient antiviral treatment for SARS-CoV-2, using the dicationic family of ILs to enhance the physicochemical properties. N 4 Yuan et al [58] have studied the use of cholinium-amino acid-based ILs (CHAAILs) to improve the solubility and permeation of poorly soluble drugs.…”
Section: And [Mp][ba]mentioning
confidence: 99%
“…Faísca et al. 57 have reported the repurposing of the antimalarial drug, hydroxychloroquine (HCQ), as an efficient antiviral treatment for SARS‐CoV‐2, using the dicationic family of ILs to enhance the physicochemical properties. N 4 ‐(7‐chloroquinolin‐4yl)‐N 1 ‐ethyl‐N 1 ‐(2‐hydroxethyl)pentane‐1,4‐diaminium bis(methanesulfonate) [HCQH 2 ][C 1 SO 3 ] 2 and N 4 ‐(7‐chloroquinolin‐4yl)‐N 1 ‐ethyl‐N 1 ‐(2‐hydroxethyl)pentane‐1,4‐diaminium bis((2S,3R,4S,5S)‐2,3,4,5,6 pentahydroxyhexanoate [HCQH 2 ][GlcCOO] 2 had water solubility and LogP values comparable to other tested HCQ‐ILs that did not demonstrate any increase in antiviral activity.…”
Section: Ils At a Glancementioning
confidence: 99%
“…On the other hand, anions of ionic liquids can be both organic and inorganic, and their nature significantly affects the properties of the entire compound. The most important feature of this group of compounds is undoubtedly an extremely wide range of applications, in which the following should be distinguished: (i) dissolution and processing of biomass [ 3 , 4 , 5 ], (ii) catalytic reactions [ 6 , 7 , 8 ], (iii) active ingredients in pharmaceutical preparations [ 9 , 10 ] or (iv) design of polymerizable monomers intended for modern material solutions [ 11 , 12 , 13 ]. The wide area of application of ionic liquids is due to their properties, among which the following should be mentioned: high thermal stability [ 14 ], high electrochemical window [ 15 ], low volatility [ 16 ] and flammability [ 17 ].…”
Section: Introductionmentioning
confidence: 99%